Peran Gereja dalam Pemberdayaan Ekonomi Jemaat Melalui Pertanian: Studi pada GKS Jemaat Pamalar - Sitaniapessy, Desy A.; Nganji, Marten U. (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Poverty remains a persistent issue that continues to attract the attention of various parties, including the church. As a social and spiritual institution, the church has a strategic role in empowering the economy of its congregation. This study aims to analyze the role of the Sumba Christian Church (GKS) Pamalar Congregation in congregational economic empowerment through the "Kebun Jemaat" program, an agriculture-based initiative. This research employs a qualitative method with a descriptive approach. Data were collected through participatory observation and in-depth interviews with church leaders and congregation members involved in the program. The findings indicate that the "Kebun Jemaat" program contributes to improving the congregation's economy by utilizing church members' land for cultivating horticultural crops, such as tomatoes and chili peppers, which are then processed into value-added products. The success of this program is supported by factors such as active involvement of the church and congregation, resource availability, and support from the government and related organizations. However, the program also faces several challenges, including land limitations due to temporary land loans, low congregation participation in crop maintenance, and a lack of capital for further business development. Therefore, more sustainable strategies are needed, such as securing permanent land ownership and enhancing congregation members' skills in agricultural business management. This study confirms that the church can play a crucial role in congregational economic empowerment through approaches based on local potential and community involvement.